MARXISM VALUES AS PORTRAYED IN STEVEN SODERBERGH’S “ERIN BROCKOVICH” MOVIE SCRIPT - Olar, Julia Sheren; Liando, Nihta V. F.; Lolowang, Imelda S. (Program Studi Pendidikan Bahasa Inggris, 2024)
The purpose of this study was find out Marxism values as portrayed in the Erin Brockovich movie script. This research discussed the value of Marxism in the movie Erin Brockovich, directed by Steven Soderbergh. This research used a qualitative method with the sociological approach. This research data was obtained from conflict problems between Erin Brockovich's character, the people of Hinkley who were victims, and the large company Pg&E. The results of this research showed that the movie Erin Brockovich depicted Marxism values. Erin Brockovich, as the main character was a representative of the lower working class who fought against large companies that had polluted the drinking water of the people around the company. The conflict that occured between them showed the results of research that illustrated Marxism Values, and two kinds of conflict that related to the application of Marxism Values in Erin Brockovich’s Movie, such as Realistic Conflict and Non Realistic Conflict. After analyzing the data the writer found the result of the research, such as; 1) Materialism 2) Social Class 3) Exploitation 4) Struggle for Social Justice. The description of Marxism values in the film Erin Brockovich was obtained by referring to Marxism literary criticism perspective and social conflict theory by Lewis Coser.